The Meaning of Marriage: - Massinai, Sitti Muthia Maghfirah (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2020)
Adolescents’ developmental tasks are including associating with peers, looking and building for self-identity, and exploring the environment. However, the number of marriage case in adolescence keeps increasing, resulting to the adolescents to face the developmental task that usually faced in early adulthood. This study explores the meaning of marriage for women who are married at <19 years of age. The study participants were three women married at <19 years old, had children, and lived in Makassar City with their partners. This research is qualitative research with a phenomenological approach. The research data were obtained using semi-structured interviews and processed using Interpretative Phenomenological Analysis (IPA). The results showed: a) Parental belief, economy, and self are the factors behind early marriage; b) Apart from cognitive aspects, emotional aspects also play a role in shaping the view of marriage; c) The changes that occur before and after marriage give rise to various types of emotions, especially changes in relationships with peers that give rise to negative emotions; d) A coping strategy that is not right makes problems that occur in married life are not appropriately resolved; and e) The spiritual aspect plays a significant role in shaping marriage commitment.